Servant leadership and research in Iceland - Gunnarsdóttir, Sigrún; Jónsdóttir, Birna Gerður (Stjórnsýslustofnun, 2013)
Servant leadership is a philosophy that sheds a new light on theories on management and leadership. Particular emphasis is on service as founded on ethics and accountability with focus on the greater good prior to narrow interests. The pioneer of the philosophy is Robert K. Greenleaf. The main characteristics of servant leadership are intrinsic interest in others, inner strength and foresight. Research on the topic has increased the past years and results show that the philosophy is positively linked to corporate social responsibility, profit as well as staff wellbeing and trust in relations. Recent studies indicate that the philosophy can be beneficial for Icelandic society. To explore this further eight surveys have been conducted in different workplaces, years 2008 – 2012. Staff views towards servant leadership of next superior were investigated using a recent Dutch instrument, SLS. Job satisfaction was measured and the link towards staff views on servant leadership. Key findings are presented showing that staff views indicate somewhat high levels of servant leadership and the highest scores are for the factors on empowerment and accountability among next superiors. Job satisfaction is overall measured high and significantly linked to servant leadership supporting prior research in other countries. Findings from the Icelandic surveys provide potentials for successful management and leadership in local workplaces but further analysis is in the process as well as comparison towards findings from other countries. Þjónandi forysta er hugmyndafræði sem varpar nýju ljósi á kenningar í stjórnunar- og leiðtogafræðum. Einstakar áherslur hennar eru þjónusta með siðfræði og ábyrgð sem grunnstoðir og hagsmuni heildar framar þrengri hagsmunum. Upphafsmaður hugmyndafræðinnar er Robert K. Greenleaf. Helstu einkenni þjónandi leiðtoga er einlægur áhugi á högum annarra, innri styrkur og framtíðarsýn. Rannsóknum um efnið hefur fjölgað undanfarin ár og sýna niðurstöður að hugmyndafræðin hefur jákvæð áhrif á samfélagslega ...